2022
DOI: 10.1186/s13102-022-00594-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of combined Action Observation Therapy with eccentric exercises in the treatment of mid-portion Achilles-tendinopathy: a feasibility pilot randomised controlled trial

Abstract: Background Mid-portion Achilles Tendinopathy (AT) is a common musculoskeletal condition with varying rehabilitation success rates. Despite the prevalence of this condition, a considerable proportion of individuals experience persisting pain and functional deficits. Current treatment approaches bias the biomedical model which emphasises physically treating and loading the tendon. Overall, there is a lack of consideration for the central nervous system that is commonly implicated in chronic injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…This was a qualitative follow-up study undertaken on a group of participants from a previous pilot feasibility randomised controlled trial which explored the effect of Action Observation Therapy with Eccentric loading in the treatment of mid-portion AT over the course of 12- weeks [ 19 ]. Two groups of participants with mid-portion Achilles Tendinopathy were compared; the intervention group watched videos of the eccentric exercises to be performed prior to performing the same exercises, while the control group watched videos of landscapes before performing the two same eccentric exercises.…”
Section: Methodsmentioning
confidence: 99%
“…This was a qualitative follow-up study undertaken on a group of participants from a previous pilot feasibility randomised controlled trial which explored the effect of Action Observation Therapy with Eccentric loading in the treatment of mid-portion AT over the course of 12- weeks [ 19 ]. Two groups of participants with mid-portion Achilles Tendinopathy were compared; the intervention group watched videos of the eccentric exercises to be performed prior to performing the same exercises, while the control group watched videos of landscapes before performing the two same eccentric exercises.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is possible to improve the brain activation area and amplitude by combing NMES with other top-down and active rehabilitation strategies or methods, thus making full use of the rehabilitation time window to achieve better treatment effects, especially for early rehabilitation phases. The mirror neuron system (MNS) plays a key role in the neural mechanism underlying motor learning-related neural plasticity, and a series of rehabilitation strategies and treatment techniques based on MNS theory have been widely applied in patients with neurological conditions and musculoskeletal disease (13,14). Mirror Neuron (MN) is a special type of neuron that is activated not only when a primate performs a movement, but also when the same or comparable action is seen (15).…”
Section: Introductionmentioning
confidence: 99%
“…In physical therapy practice, the above MNS-based rehabilitation strategies are usually used in combination. For example, observation and following the performance of target movements are commonly used in therapeutic exercise practice (14). In addition, a published article showed that brain regions activated by NMES and FES overlap with the cortical areas that participate in AE and MI processes (9,25).…”
Section: Introductionmentioning
confidence: 99%
“…This was a double-blind, randomized controlled trial focused on the effectiveness or differences between the eccentric exercise protocol and low-intensity flow-restricted training. The CONSORT 2016 guideline for randomized clinical trials was used [25].…”
mentioning
confidence: 99%